Application of Force to a Syndecan-4 Containing Complex With Thy-1–αVβ3 Integrin Accelerates Neurite Retraction - Burgos-Bravo, Francesca; Martínez-Meza, Samuel; Quest, Andrew F. G.; Wilson, Christian A. M.; Leyton, Lisette (Frontiers in Molecular Biosciences, 2020)
Inflammation contributes to the genesis and progression of chronic diseases, such as cancer and neurodegeneration. Upregulation of integrins in astrocytes during inflammation induces neurite retraction by binding to the neuronal protein Thy-1, also known as CD90. Additionally, Thy-1 alters astrocyte contractility and movement by binding to the mechano-sensors V3 integrin and Syndecan-4. However, the contribution of Syndecan-4 to neurite shortening following Thy-1–V3 integrin interaction remains unknown. To further characterize the contribution of Syndecan-4 in Thy-1-dependent neurite outgrowth inhibition and neurite retraction, cell-based assays under pro-inflammatory conditions were performed. In addition, using Optical Tweezers, we studied single-molecule binding properties between these proteins, and their mechanical responses. Syndecan-4 increased the lifetime of Thy-1–V3 integrin binding by interacting directly with Thy-1 and forming a ternary complex (Thy-1–V3 integrin+Syndecan-4). Under in vitro-generated pro-inflammatory conditions, Syndecan-4 accelerated the effect of integrin–engaged Thy-1 by forming this ternary complex, leading to faster neurite retraction and the inhibition of neurite outgrowth. Thus, Syndecan-4 controls neurite cytoskeleton contractility by modulating V3 integrin mechano-receptor function. These results suggest that mechano-transduction, cell-matrix and cell-cell interactions are likely critical events in inflammation-related disease development.